2015
DOI: 10.1155/2015/349215
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screening of Gene Function and Networks by DNA Microarray Analysis in Japanese Patients with Idiopathic Portal Hypertension

Abstract: The functions of genes involved in idiopathic portal hypertension (IPH) remain unidentified. The present study was undertaken to identify the functions of genes expressed in blood samples from patients with IPH through comprehensive analysis of gene expression using DNA microarrays. The data were compared with data from healthy individuals to explore the functions of genes showing increased or decreased expression in patients with IPH. In cluster analysis, no dominant probe group was shown to differ between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…In addition, a female patient's mother also suffers from IPH, which lead us to wonder whether it is related to the gene. Similar to some reports, [26][27][28] we speculate that mutation of some genes may render the patients susceptible to IPH, which may be exacerbated by environmental or lifestyle-related factors and promote occurrence of IPH. Among the 138 patients with ANA records, 25 patients were ANA positive, and 72% of these patients were female.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, a female patient's mother also suffers from IPH, which lead us to wonder whether it is related to the gene. Similar to some reports, [26][27][28] we speculate that mutation of some genes may render the patients susceptible to IPH, which may be exacerbated by environmental or lifestyle-related factors and promote occurrence of IPH. Among the 138 patients with ANA records, 25 patients were ANA positive, and 72% of these patients were female.…”
Section: Discussionsupporting
confidence: 89%
“…[7][8][9][10] The etiology of IPH is still not clear. Some of the proposed etiological factors have included immunologic disorders, [11][12][13][14][15][16] chronic infection with some bacteria or human immunodeficiency virus, 13,[17][18][19] medication and toxins, [20][21][22][23][24] gene mutation, [25][26][27][28][29] and some other etiologies like dialysis. 30 The main clinical symptoms of IPH are those caused by portal hypertension, including splenomegaly, hypersplenism, hepatomegaly, gastrointestinal bleeding, ascites, and portal vein thrombosis (PVT).…”
Section: Introductionmentioning
confidence: 99%
“…Seropositivity for antinuclear, antimicrosomal and anti-DNA antibodies has also been reported [ 3 , 23 ]. The underlying mechanism of immune-induced injury to the sinusoidal microvasculature is unclear but it appears to be related to hyperactivation of intrasinusoidal T lymphocytes [ 26 , 35 ].…”
Section: Pathophysiology and Etiologic Associationsmentioning
confidence: 99%
“…One previous study using microarray determined gene expression profiles in blood samples from patients with idiopathic portal hypertension 38 . The study showed up-regulation of genes that are involved in the actin cytoskeleton, actin binding and cytoskeletal protein binding 38 as well as down-regulation of genes primarily related to the immune system, suggesting immunological abnormalities in idiopathic portal hypertension 38 . Similarly, our functional annotation analyses indicated increased actin cytoskeleton (Fig.…”
Section: Discussionmentioning
confidence: 99%